L’insertion professionnelle de nouveaux enseignants : une recension systématique de la littérature - Ndzeno, José; Sénéchal, Carole; Larivée, Serge (Canadian Journal of Education/Revue canadienne de l’éducation, 2024)
The early dropout rates of teachers is a much-discussed issue in several industrialized countries such as Canada, where dropout rates of over 50% can occur among novice teachers. The aim of this article is to identify the induction support strategies offered to novice teachers and to carry out a qualitative analysis in order to assess their effectiveness in helping teachers to solve the attrition problem. The results show that school administration responsibility is crucial, whether in training mentors and novice teachers, or in ensuring that the induction program is properly implemented and runs smoothly. This systematic literature review also shows that, when mentoring, if the most popular form of dyadic support is properly administered and management is informed of its effectiveness, both contribute significantly to the retention of novice teachers. In conclusion, this review has highlighted the fact that many mentors do not receive appropriate training to carry out their mission, and that expectations from the school administration regarding their roles and responsibilities often remain unclear.